2015
DOI: 10.1001/jamaoto.2015.2200
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Risk Estimation for Postoperative Complications After Surgery for Oral Cavity Cancer

Abstract: IMPORTANCE Postoperative complications after head and neck surgery carry the potential for significant morbidity. Estimating the risk of complications in an individual patient is challenging. OBJECTIVE To develop a statistical tool capable of predicting an individual patient’s risk of developing a major complication after surgery for oral cavity squamous cell carcinoma. DESIGN, SETTING, AND PARTICIPANTS Retrospective case series derived from an institutional clinical oncologic database, augmented by medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(52 reference statements)
0
15
0
1
Order By: Relevance
“…The process of identification and recording of complications was as described by previous work at our institution(11, 12). All events that occurred in the patient’s record within 45 days of surgery, either in medical, nursing, anesthetic or allied health professional documentation was compared to the definition of a post-operative complication.…”
Section: Methodsmentioning
confidence: 99%
“…The process of identification and recording of complications was as described by previous work at our institution(11, 12). All events that occurred in the patient’s record within 45 days of surgery, either in medical, nursing, anesthetic or allied health professional documentation was compared to the definition of a post-operative complication.…”
Section: Methodsmentioning
confidence: 99%
“…However, HNSCC patient stage, from I to IV, is only based on TNM stage. Consideration of other clinicopathologic factors like age, sex, tumor site and treatment, which are associated with HNSCC patient survival [1013], is necessary for accurate prognostic analyses. Therefore, our prognosis predictions included age, sex, race, tumor site, surgery and radiotherapy, along with TNM stage.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies consisted of males who suffered from a higher incidence of postoperative complications, such as systemic disease, flap complications, infection, and hemorrhage . However, Loupatatzi concluded that female patients have a higher risk of developing complications than males in free flap reconstruction due to a higher rate of systemic diseases in females in his study.…”
Section: Discussionmentioning
confidence: 91%
“…Additional studies should be conducted to identify potential underlying mechanisms that explain differences in sex, such as cigarette and alcohol use. Patel, Bhattacharyya, and Awad found that postoperative complications are related to older age and that the incidence rate increases with age. However, Wu and Thomas found that aging is not a risk factor.…”
Section: Discussionmentioning
confidence: 99%